Penerapan Aplikasi Keuangan Berbasis Android Si Apik Dalam Penyusunan Laporan Keuangan Berdasarkan SAK EMKM - Lalu Hasan Habibi; Iyeh Supriatna (Indonesian Accounting Literacy Journal, 2021)
Abstract: The application of accounting information systems in companies is important because it can present reliable information effectively and efficiently so as to facilitate operational activities to decision making. Currently, many companies are constrained in presenting accounting information systems in the form of recording transactions and financial statements based on SAK EMKM. Transaction recording and financial statements with SAK EMKM can be done on Android-based accounting software via smartphone devices. This research helps Qaya Laundry provide easy transaction recording and financial reporting using the Si Apik android-based financial accounting application. The method used in this study is based on a qualitative descriptive method with data collection through observation, interviews, and documentation approaches. The results of this study are in the form of guidelines for implementing the Si Apik application in recording transactions and preparing financial reports, making it easier for Qaya Laundry to manage finances for future decision-making needs.